Prospects for the Development of Fergana Economic Geographical Region and the Importance of Transport in it - o’g’li, Abdugofurov Shoxjaxon Muxammadqobul (Research Parks Publishers, 2023)
Fergana Valley, one of the ancient and densely populated regions, is surrounded on three sides by the Pamir-Aloy, Tianshan, and Fergana ranges. It was the basis for the accumulation of population settlements. The area of the valley, which is not very large, is only 4% of the territory of the republic. This article describes in detail the development prospects of Fergana economic geographical region.